Optimization and Validation of Clobazam Content Determination Method in Tablet Preparations Using High Performance Liquid Chromatography (HPLC) - Agustina, Rosita; Mulyadi, Dikdik; Yuningsih, Lela Mukmilah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Clobazam is a tablet-shaped drug whose concentration was analyzed using the HPLC separation method. Analysis of clobazam concentration using a method in accordance with FI VI, with a mobile phase composition of 70 mL of water and 30 mL of acetonitrile, resulting in a retention time of 21 minutes. The purpose of this study was to obtain the most optimal composition of the mobile phase and column to obtain a faster retention time in the analysis of clobazam levels. As well as to validate the analysis method whose results are in accordance with the validation requirements in the Indonesian pharmacopoeia VI. Data were analyzed using linearity tests, specificity or selectivity tests, accuracy tests, repeatability and intermediate precision tests, robustness tests, and LOS and LOQ tests. The results showed a theoretical plate number of 1711.5, a tailing factor of 1.34, and a retention time of 1.69 minutes using a C18 column measuring 150 x 3 mm 3 μm with a mobile phase ratio of acetonitrile: water of 80:20. The validation results of the analytical method for accuracy, precision, selectivity, and robustness showed RSD <2%, Detection Limit (LOD) 0.0014 mg/mL, Quantification Limit (LOQ) 0.0042 mg/mL, and the linearity test results showed a correlation coefficient of 0.999, meeting the FI VI validation criteria. The conclusion is that differences in the composition of the mobile phase and the particle size of the column greatly affect the characteristics of the chromatogram produced in HPLC analysis.